Development of consensus recommendations on the management of vitiligo and the role of decapeptide in vitiligo by the delphi method - Davinder Parsad; Sanjeev Kandhari; Rachita Dhurat; Bela Shah; Imran Majid; Harikishan Kumar Yadalla; Jagdish Sakhiya; Shital Poojary; P Jagadish; Pravin D Banotkar; Ravindra Babu; Y M Shivakumar; et al. (Indian Journal of Dermatology, 2023)
Background: Treatment of vitiligo is still a challenge in dermatology. Literature is sparse on the definitive clinical role of basic fibroblast growth factor (bFGF) in vitiligo patients. Aims: We decided to generate a consensus in an attempt to answer some critical questions related to the management of vitiligo and the role of bFGF. Materials and Methods: A Delphi method among 21 experts across India was conducted. A consensus (agreement was 75% or greater) was taken on 27 statements on the prevalence, epidemiology, and treatment of vitiligo and the role of bFGF in the management of vitiligo. The consensus process was completed after two rounds. Results: Topical corticosteroid therapy is the first-line therapy for vitiligo; however, its adverse effects are widely known, especially in sensitive areas. Topical calcineurin inhibitors are preferred in stable vitiligo of the face, neck, genitals, or intertriginous regions as an alternative to topical corticosteroids. Topical bFGF is a relatively newer therapy with a promising role in stable vitiligo. bFGF is safe and effective in inducing repigmentation of vitiligo lesions. Combination therapy of bFGF with other topical therapies, phototherapy, and surgical procedures can be beneficial in patients of vitiligo. Conclusion: This consensus would complement the currently available literature on bFGF and help the practitioner to recognize the unmet need in the treatment of vitiligo.